Sub-decadal diatom oxygen isotope record and biogeochemical data of the last 220 years (2015-1790CE) based on a sediment short core from Lake Khamra, Yakutia, Siberia ... - Stieg, Amelie; Biskaborn, Boris K; Herzschuh, Ulrike; Strauss, Jens; Pestryakova, Luidmila A; Meyer, Hanno (PANGAEA, 2024)
The multiproxy data set from the Russian Lake Khamra (59.99°N, 112.98°E, 340 m a.s.l.), located in Eastern Siberia in SW Yakutia, comprise the following data: (1) Gapless and high-resolution diatom oxygen isotope (δ18Odiatom) measurements of 39 samples from sediment short core EN18232-1, Lake Khamra, and corresponding key geochemical characteristics. (2) Radiometric age dating results for 210Pb and 137Cs (Pb/Cs) as well as (3) radiocarbon age dating results of the short core EN18232-1, Lake Khamra. (4) Biogeochemical measurement results, including total mercury concentrations (THg) and (5) total inorganic carbon (TiC) of the short core EN18232-1. (6) Isotopic data from lake water, ice and snow samples, obtained during two field campaigns at Lake Khamra in August 2018 and March 2020 (EN18232-1, EN20001, EN20015, EN20016). More detailed information about the age-depth modelling, the isotope measurements and the biogeochemical analyses can be found in the individual abstracts and the corresponding research ...